MENGGUGAT PENUNJUKKAN PENJABAT (Pj) KEPALA DAERAH TANPA PEMILIHAN:: Tergerusnya Kedaulatan Rakyat dan Menguatnya Dominasi Pemerintah Pusat - Laode Harjudin; La Tarifu; Harnina Ridwan; La Ode Muhammad Elwan (Journal Publicuho, 2022)
This study explains the question of what are the implications of appointing acting regional heads for the principles of democracy in Indonesia? To explain this problem, the study uses the theory of popular sovereignty as one of the main principles in democracy. This research uses the method used in writing this study is library research which contains ideas and concepts that are substantial with research problems. The results of the study show that the appointment of acting Regional Heads returns the centralization of power to the central government by ignoring the principle of popular sovereignty as the essence of democracy. Concretely, the appointment of acting Regional Heads raises three forms of setbacks in democracy, namely, the return to centralization of power in the hands of the central government, the erosion of people's participation, the justification for abolishing regional elections, and the decline of the essence of people's sovereignty. This appointment mechanism certainly provides political advantages for the government and its supporters for the benefit of 2024, both in elections and regional elections. This condition increasingly provides an opportunity for the central government to control the process of implementing the 2024 elections and local elections.